Ischaemic heart disease: stable angina. (July 2022) - Gabara, Lavinia; Olsen, Sally; Alaour, Bashir; Curzen, Nick
Abstract: Stable angina is a clinical syndrome reflecting inadequate myocardial perfusion. This is typically, but not always, caused by atherosclerotic coronary artery disease. A detailed history is important to establish the diagnosis, presence of risk factors and unstable symptoms. A range of tests is available to investigate patients with stable angina. Anatomical tests, including CT coronary angiography and invasive coronary angiography, aim to assess the presence and extent of atheroma or structural coronary abnormalities. CT coronary angiography/coronary angiography with fractional flow reserve assessment, aims to detect the presence and extent of coronary flow insufficiency. Stress echocardiography, stress cardiac MRI and nuclear perfusion scans aim to assess territorial myocardial ischaemia and viability. Appropriate drug therapy can potentially improve symptoms and prognosis. Risk stratification requires the integration of age, risk factors, anatomical distribution and characteristics of coronary disease and ventricular function. Revascularization should be considered to improve symptoms when angina has a significant impact on the person's quality of life despite optimal medical therapy, or to improve prognosis in certain settings. The choice of revascularization method (percutaneous coronary intervention or coronary artery bypass graft) is influenced by the extent and complexity of disease, presence of co-morbidities, bleeding risk and patient preference.